EVALUASI KESESUAIAN PENILAIAN SUMATIF AKHIR JENJANG KELAS XII DENGAN DISTRIBUSI RANAH KOGNITIF DALAM KURIKULUM MERDEKA - Muhammad Jahfal Hanan; Maulana Phaundra Tegar Irawan; Deby Luriawati Naryatmojo; Wagiran (Jurnal Bastra (Bahasa dan Sastra), 2025)
The Merdeka Curriculum aims to give freedom to educational institutions and teachers in designing learning that suits the needs and characteristics of students. In addition, this curriculum also directs the development of student character and skills, not just centered on achieving test scores. So the Minister of Education, Culture, Research and Technology issued a decree to implement the independent curriculum which is listed in the Decree of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia number 262 / M / 2022. Based on the implementation of the independent curriculum that has been running from 2022, there has not been much discussion about the suitability of the PSAJ in terms of the distribution of the cognitive domain. The research to be carried out uses a type of qualitative research with a descriptive approach. The research will be carried out by determining the object of research on purpose, so the technique used is Purposive Sampling. The suitability of PSAJ to the distribution of cognitive domains when viewed from the percentage of each school, S01 has a distribution of Low Order Thinking Skills (LOTS), the percentage in S02 shows the assessment of PSAJ which has a level of High Order Thinking Skills (HOTS), while in S03, represents the level of test items Middle Thinking Skills (MOTS) and High Order Thinking Skills (HOTS). The knowledge dimension that is often presented is the conceptual dimension, which indicates that the questions attempt to improve learners' conceptual understanding. The thing that needs to be considered in making questions is of course not to be separated from the AKM and the need for the suitability of the level of thinking according to the ability of students.